Safety of augmentation cystoplasty in patients with bladder abnormalities undergoing renal transplantation: a systematic review (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND Augmentation cystoplasty (AC) has been recently proposed to improve a bladder condition before or after a renal transplantation for an optimal allograft function. Until now, AC in adults with end-stage renal disease (ESRD) is uncommon and rarely practiced. This study aimed to investigate the safety of AC in patients with bladder abnormalities who required renal transplantation. METHODS Studies of patients with ESRD and abnormal bladder who underwent AC were searched in ProQuest, PubMed, EBSCO, and Cochrane Library online databases. Only studies published in English from January 1985 to May 2020 were included. The keywords used were renal transplantation, bladder dysfunction, cystoplasty, and their synonyms. Data were extracted by two independent authors who selected, screened, and assessed the articles’ eligibility and quality. The outcomes were graft survival rate and complications of AC. RESULTS A total of 19 articles were included. AC improved an intravesical pressure, a bladder capacity, and a compliance in patients with ESRD and bladder abnormalities, allowing patients to undergo the renal transplantation. Even though AC in patients with renal transplantation resulted in a significantly higher urinary tract infection rate than patients who underwent renal transplantation only, performing AC after renal transplantation was considered safe. CONCLUSIONS AC was considered safe for patients with bladder abnormalities who underwent renal transplantation.